Comparison of Levitt's CO breath test and the 15N‐glycine labeling technique for measuring the lifespan of human red blood cells. Issue 10 (4th August 2021) - Ye, Lei; Ji, Yongqiang; Zhou, Cong; Luo, Junfeng; Zhang, Li; Jing, Liping; Zhao, Xin; Guo, Jie; Gao, Qingyan; Peng, Guangxin; Li, Yang; Li, Yuan; et al.
Abstract: The red blood cell (RBC) lifespan is an important physiological indicator of clear significance in clinical research, used for the differential diagnosis of various diseases such as anemia, compensatory phase hemolysis, and polycythemia. The 15 N‐glycine labeling technique is the gold standard method for determining RBC lifespans. However, the usefulness of this technique in clinical settings is seriously hindered by the several weeks required to complete the analyses. Levitt's CO breath test is another reliable technique for determining RBC lifespans, with a simpler protocol giving much faster results, making it more useful in clinical applications. We compared the CO breath test and 15 N‐glycine labeling technique for measuring the human RBC lifespan. We investigated human RBC lifespans where each subject undertook both the 15 N‐glycine labeling technique and the CO breath test. The correlation between the results from these two methods was analyzed. Eight of the ten subjects successfully completed the study. The RBC lifespan values obtained by Levitt's CO breath test were lower than those obtained by the 15 N‐glycine labeling technique. The RBC lifespan values determined from the 15 N‐glycine labeling technique and the CO breath test were significantly correlated, with a Pearson correlation coefficient of R = 0.98 ( p  < 0.05), while the R 2 of the linear regression equation was 0.96. The CO breath test exhibits as good performance as the 15 N‐glycine labelling technique in distinguishing healthy subjects from subjects with hemolysis. The result suggests that the CO breath test is a reliable method for quickly determining human RBC lifespans in clinical applications.